PREPARATION OF RABBIT POLYCLONAL ANTIBODIES AGAINST GFP AND MCHERRY PROTEINS - Turgimbayeva, A.; Baltabekova, M.; Yelyubay, A.; Ibrayeva, A.; Mussakhmetov, A.; Abeldenov, S.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2014)
The aim of this study is to get polyclonal antibodies against GFP and mCherry recombinant proteins. Bacterial strain producers of fluorescent proteins were obtained due to transformation of Escherichia coli with the prepared expression vectors: pET-28c/gfp and pET-28c/mcherry. After 16 hours of induction GFP and mCherry were extracted by method of metal-chelate affinity chromatography from bacterial cultures. The extracted proteins possessed 98% of electrophoretic degree of purity, as well as the high concentration of the proteins in fractions provides intense glow of the proteins under ultraviolet light. Rabbits were immunized with the recombinant proteins GFP and mCherry, from serum of which corresponding immunoglobulins were purified by 35% of ammonium sulfate precipitation. The concentration of antibodies after purification was 4.4 µg/µl. The optimal dilution and the specificity of anti-GFP and anti-mCherry antibodies were confirmed by total proteins extracts of bacterial, yeast-derived and HEK293 cells.